KEPENTINGAN AUSTRALIA DALAM MEMBERLAKUKAN LARANGAN IMPOR BAGI PRODUK APEL SELANDIA BARU - Prayanti, Ida Ayu Adi; Sushanti, Sukma; Widya Nugraha, A. A. Bagus Surya (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2019)
ABSTRACT This research aims to describe Australia's national interest in enforcement of import ban of New Zealand apple products. This was triggered by the spread of fire blight pests in Auckland, New Zealand in 1919. The negotiation process between the Australian Government and New Zealand was carried out from 1986 to 2008. The Australian Government imposed the import ban based on the Australian Quarantine Policies 1908 specifically referring to scientific research reports in Final Import Risk Analysis. This research used qualitative descriptive method. Data were collected from various resources including library sources, news and reports. Data were analyzed with the concept of National Interest and Protectionism in International Trade. This research shows a ban on imports of New Zealand apple products is to establish economic interest, especially in an effort to protect the domestic market. Keywords: Australia, Quarantine Policies, Protectionism in International Trade, National Interest